The Effect Work Motivation, Training, and Organization Culture on the Performance of Production Employees at PT. EK Bogor District - Ajeng, Marinda (MultiTech Publisher, 2024)
This research was conducted to determine the influence of workk motivation, training, and organizational culture on the performance of profuction employees at PT. EK. The sample used was 40 people using purposive sampling. Validity test results on all variables rcount ≥ 0.3. This means that the data is valid. Meanwhile, in the reliability test for all variables rcount ≥ 0.6. This means that data is reliable. The results of multiple linear regression analysis show that work motivation, training, and organizational culture have a positive effect on employee performance. The multiple correlation test shows a figure of 0.903, meaning that it is known that there is a very strong and positive relationship between work motivation, training, and organizational culture, and employee performance. The R2 result is 81,5% of employee performance is influenced by work motivation training, and organizational culture. The results of hypothesis testing state that simultaneously and partially work motivation, training, and significant effect on employee performance.